Cellular responses at the application site of a high-density microarray patch delivering an influenza vaccine in a randomized, controlled phase I clinical trial. - Alexandra C I Depelsenaire (Public Library of Science (PLoS), 2021)
Microarray patches (MAPs) have the potential to be a safer, more acceptable, easier to use and more cost-effective method for administration of vaccines when compared to the needle and syringe. Since MAPs deliver vaccine to the dermis and epidermis, a degree of local immune response at the site of application is expected. In a phase 1 clinical trial (ACTRN 12618000112268), the Vaxxas high-density MAP (HD-MAP) was used to deliver a monovalent, split inactivated influenza virus vaccine into the skin. HD-MAP immunisation led to significantly enhanced humoral responses on day 8, 22 and 61 compared with IM injection of a quadrivalent commercial seasonal influenza vaccine (Afluria Quadrivalent®). Here, the aim was to analyse cellular responses to HD-MAPs in the skin of trial subjects, using flow cytometry and immunohistochemistry. HD-MAPs were coated with a split inactivated influenza virus vaccine (A/Singapore/GP1908/2015 [H1N1]), to deliver 5 μg haemagglutinin (HA) per HD-MAP. Three HD-MAPs were applied to the volar forearm (FA) of five healthy volunteers (to achieve the required 15 μg HA dose), whilst five control subjects received three uncoated HD-MAPs (placebo). Local skin response was recorded for over 61 days and haemagglutination inhibition antibody titres (HAI) were assessed on days 1, 4, 8, 22, and 61. Skin biopsies were taken before (day 1), and three days after HD-MAP application (day 4) and analysed by flow-cytometry and immunohistochemistry to compare local immune subset infiltration. HD-MAP vaccination with 15 μg HA resulted in significant HAI antibody titres compared to the placebo group. Application of uncoated placebo HD-MAPs resulted in mild erythema and oedema in most subjects, that resolved by day 4 in 80% of subjects. Active, HA-coated HD-MAP application resulted in stronger erythema responses on day 4, which resolved between days 22-61. Overall, these erythema responses were accompanied by an influx of immune cells in all subjects. Increased cell infiltration of CD3+, CD4+, CD8+ T cells as well as myeloid CD11b+ CD11c+ and non-myeloid CD11b- dendritic cells were observed in all subjects, but more pronounced in active HD-MAP groups. In contrast, CD19+/CD20+ B cell counts remained unchanged. Key limitations include the use of an influenza vaccine, to which the subjects may have had previous exposure. Different results might have been obtained with HD-MAPs inducing a primary immune response. In conclusion, influenza vaccine administered to the forearm (FA) using the HD-MAP was well-tolerated and induced a mild to moderate skin response with lymphocytic infiltrate at the site of application.